Impact of freshwater diversions on vegetation in coastal wetlands based on remote sensing derived vegetation index - Wu, Wei; Grimes, Evan; Suir, Glenn (Frontiers in Marine Science, 2023)
There exist contrasting results on the impact of large-scale freshwater and sediment diversions on land gain/loss. To improve understanding on the efficacy of diversion projects in restoring coastal wetlands, we aim to evaluate the long-term impacts of diversion-altered salinity and water level on vegetation productivity in coastal wetlands. Two freshwater diversion projects Caernarvon and Davis Pond in Louisiana, U.S. and associated reference sites were selected for inclusion in this study. We implemented multi-level Bayesian models to evaluate 1) how vegetation productivity approximated by Landsat-derived Normalized Difference Vegetation Index (NDVI) in peak biomass season changed over time (pre- and post-construction and operation of the freshwater diversions), and 2) how peak-season NDVI responded to mean and variability of water level and salinity among a suite of factors that could affect vegetation productivity. Analysis showed difference in temporal trends of NDVI between the reference and diversion site for the Caernarvon project with a significant increase at the diversion site although NDVI negatively responded to diversion at the beginning. Diversion did not seem to negatively affect NDVI for the Davis Pond project and NDVI only marginally increased at the diversion site. For both projects, NDVI negatively responded to water level, while salinity negatively affected NDVI or showed quadratic relation with NDVI. At the Caernarvon diversion project, the negative impact of water level on NDVI was greater at the diversion site than at the reference site. At the Davis Pond project, it was the salinity that showed different impact between the diversion and reference site. The temporal increase of NDVI at the Caernarvon diversion site can be explained by the lower salinity driven by diversion. The quadratic relation between salinity and NDVI at the Davis Pond diversion project led to only marginal increase at the diversion site. This study provided uncertainty estimates in temporal trend of NDVI and the impact of two key abiotic drivers on NDVI. The improved understanding on vegetation productivity will help predict landscape change in response to freshwater diversions.